Digital mosque management strengthening workshop to enhance the competence of mosque administrators in Malang City - Arif Hidayat; Ahmad Taufiq; Sunaryono Sunaryono; Munzil Munzil; Helmi Muhammad; ST. Ulfawanti Intan Subadra (Community Empowerment, 2024)
In recent years, mosques have primarily served as places of worship, neglecting their ten additional roles and functions. This stems from the limited understanding of mosque administrators (takmir masjid). This community service initiative aimed to enhance the competence of takmir masjid in management, digitalization, and mosque economic empowerment, targeting mosque administrators in Malang City. The activities employed included lectures, discussions, and hands-on training. The outcomes revealed a significant improvement in takmir masjid competence, particularly in utilizing MOSQ for mosque management. Besides enhancing mosque management systems, the broader community can now easily access online information about mosques.